2018
DOI: 10.1155/2018/2314794
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Conductive BNC/PPy·CuCl2 Hybrid Flexible Nanocomposites by In Situ Polymerization

Abstract: This work reports the one-step synthesis of bacterial nanocellulose (BNC) incorporated with polypyrrole (PPy) by chemical in situ polymerization of pyrrole (Py) using CuCl2·2H2O as both oxidant agent and functional component, varying the concentration and molar ratio. Electrical, morphological, and physical-chemical properties of these nanocomposites were investigated. The results revealed that with the increase of Py concentration and molar ratio, the nanocomposites presented traces of copper chloride and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Therefore, Daliana Muller et al formed BNC/PPy.CuCl 2 nanocomposite by one step in situ oxidative polymerization using CuCl 2 dehydrate as an oxidant and conducting material in the nanocomposite having 0.04 and 0.08molL -1 of pyrrole concentration. The authors found that as the pyrrole concentration increased from 0.04 to 0.08molL -1 for a 2:1 M ratio, there was an increase in PPy incorporation into the BNC matrix [ 117 ]. The synthesis of a composite comprising polypyrrole (PPy) quantum dots and graphene oxide (GO), denoted as PPy/GO, is achieved through an in situ polymerization process by Hamid et al [ 118 ].…”
Section: Preparation Of Polypyrrole Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Daliana Muller et al formed BNC/PPy.CuCl 2 nanocomposite by one step in situ oxidative polymerization using CuCl 2 dehydrate as an oxidant and conducting material in the nanocomposite having 0.04 and 0.08molL -1 of pyrrole concentration. The authors found that as the pyrrole concentration increased from 0.04 to 0.08molL -1 for a 2:1 M ratio, there was an increase in PPy incorporation into the BNC matrix [ 117 ]. The synthesis of a composite comprising polypyrrole (PPy) quantum dots and graphene oxide (GO), denoted as PPy/GO, is achieved through an in situ polymerization process by Hamid et al [ 118 ].…”
Section: Preparation Of Polypyrrole Compositesmentioning
confidence: 99%
“…Muller et al found that with an increase in PPy concentration, electrical conductivity also increased from 1.64 × 10 −4 to 1.54 × 10 −3 S/cm for the 2:1 M ratio 2:1 which further got enhanced with an increase in molar ratio as shown in Table 1 which can be due to the rise in the concentration of copper chloride [ 117 ]. Xie et al studied the effect of the Py/FeCl 3 ratio on the resistivity of the PPy/cotton compound, as shown in Table 2 , and found that 2:1 is the optimum ratio.…”
Section: Properties Of Polypyrrole Compositementioning
confidence: 99%